Study on Keeping Quality and Cryopreservability of Buffalo Semen in Egg Yolk and Soybean Based Extenders - Chaudhari, D.V.; Dhami, A.J.; Hadiya, K.K.; Patel , J.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The study was aimed to compare efficacy of egg yolk based diluent (TFYG) with soybean based commercial diluents (Bioxcell® and Optixcell®, IMV, France) for refrigeration and cryopreservation (-196°C) of six Surti buffalo semen. Each qualified ejaculate (n=8/bull, >70% initial motility) was split diluted @ 100 ×106 sperm ml-1 at 34°C with 3 diluents. Part of each aliquot was filled in French mini straws and rest transferred to refrigerator for gradual cooling to 4-5°C. After 4 h of equilibration at 4-5°C in cold handling cabinet, the straws were frozen using programmable bio-freezer. The initial mean motility, acrosome integrity and hypo-osmotic reactive sperm per cent of fresh semen were 78.54±0.30, 94.40±0.20 and 79.35±0.42%, respectively. Sperm progressive motility at 24 hrs of refrigeration storage was 68.33±0.45, 66.25±0.46 and 70.31±0.46 %, and at 72 hrs of refrigeration storage 52.50±0.68, 48.54±0.84 and 53.85±0.75 % in TFYG, Bioxcell and Optixcell diluents, respectively. Acrosomal integrity and hypo-osmotic reactivity at 24 hrs of refrigeration storage were 88.15±0.18, 87.25±0.21, 89.27±0.20% and 66.04±0.50, 63.81±0.45, 68.10±0.46%, whereas at 72 hrs of refrigeration, the values were 81.67±0.23, 80.60±0.30, 82.83±0.27% and 51.35±0.60, 47.35±0.68, 53.40±0.68%, respectively, in above 3 diluents. The pre-freeze sperm progressive motility recorded in TFYG, Bioxcell and Optixcell diluents was 69.48±0.37, 68.02±0.49 and 70.94±0.38%, and post-thaw motility was 47.71±0.79, 44.38±0.85 and 49.90±0.90%, respectively. Per cent sperm acrosomal integrity and hypo-osmotic reactivity in TFYG, Bioxcell and Optixcell diluents were 89.54±0.18, 88.58±0.22, 90.52±0.21% and 67.96±0.32, 65.65±0.42, 70.23±0.37% at pre-freeze stage, whereas 76.83±0.23, 75.90 ±0.27, 78.50±0.25% and 45.02±0.84, 42.31±0.82, 47.81±0.90% at post-thaw stage, respectively. The post-thaw longevity after 60 minutes of incubation (37°C) was 35.52±0.79, 31.15±0.85, 37.19±0.81%, respectively, in above 3 diluents. Among the three semen diluent percent sperm progressive motility, acrosomal integrity and hypo-osmotic reactivity at particular stage were higher in Optixcell showing at par results in TFYG, whereas Bioxcell showed significantly (P<0.05) lower findings than other two diluents. Optixcell is a commercial product much costlier than TFYG, hence there is a need to develop local soybean based semen extender which can give comparable results with TFYG.